2013
DOI: 10.1063/1.4844915
|View full text |Cite
|
Sign up to set email alerts
|

Effective lifetimes exceeding 300 μs in gettered p-type epitaxial kerfless silicon for photovoltaics

Abstract: We evaluate defect concentrations and investigate the lifetime potential of p-type single-crystal kerfless silicon produced via epitaxy for photovoltaics. In gettered material, low interstitial iron concentrations (as low as (3.2 ± 2.2) × 109 cm−3) suggest that minority-carrier lifetime is not limited by dissolved iron. An increase in gettered lifetime from <20 to >300 μs is observed after increasing growth cleanliness. This improvement coincides with reductions in the concentration of Mo, V, Nb,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 73 publications
1
32
0
Order By: Relevance
“…The first 2D Model consists of heterogeneously distributed dislocations and no grain boundaries, representing mono-like [52][53][54][55][56][57][58][59] and epitaxial silicon [60][61][62][63]. The second 2D Model adds a grain boundary to the dislocations, simulating conventional multicrystalline silicon (mc-Si).…”
Section: B3smentioning
confidence: 99%
“…The first 2D Model consists of heterogeneously distributed dislocations and no grain boundaries, representing mono-like [52][53][54][55][56][57][58][59] and epitaxial silicon [60][61][62][63]. The second 2D Model adds a grain boundary to the dislocations, simulating conventional multicrystalline silicon (mc-Si).…”
Section: B3smentioning
confidence: 99%
“…Taking the minimum bulk lifetime of 350 ms, the corresponding minimum minority carrier diffusion length is $ 670 mm (4 16 times the silicon thickness), which is the highest reported so far in thin ( o 50 mm) epitaxial n-type silicon films, to the best of our knowledge. Powell et al have reported an effective lifetime of $ 343 ms in much thicker (95 mm), gettered, p-type epitaxial wafers [39]. Further improvements to the material quality using various novel porous silicon templates (not presented here) and to surface passivation procedure have been made which has resulted in even higher effective lifetimes of $ 700 ms at the injection level of 10 15 cm À 3 .…”
Section: Towards Achieving High Minority Carrier Diffusion Lengths Inmentioning
confidence: 88%
“…The carried by thick polycrystalline Si as a drop replacement for conventional Si wafers Verena Steckenreiter 1 , Jan Hensen 1 , Jan Hendrik Petermann 1 -Si passivates the functions as a reflector. Openings in the a PERL-type rear wafer surface is (100)-an absorption short circuit current density of (38.5±0.…”
Section: Introductionmentioning
confidence: 99%
“…Epitaxy of thin-film crystalline Si layers enables high lifetimes [1] and high cell efficiencies re-use of the growth template [3,4] ensures a high lower the production cost of future ultraHowever, thin large-area layers (<50 µm) are fragile and thus require specialized handling in cell and module This technology is thus hardly compatible with currently existing cell production equipment.…”
Section: Introductionmentioning
confidence: 99%